Community Education on the Benefits of Natural Antioxidants in Green Tea Leaf-Based Sunscreen Gel for Skin Protection - Sinurat, Jhon Patar; Br Karo, Reh Malem (JURNAL PENGMAS KESTRA (JPK), 2025)
Ultraviolet (UV) radiation is one of the key contributors to the deterioration of skin structure and function. Its harmful effects include premature aging, hyperpigmentation, and increased risk of skin cancer. One of the underlying mechanisms of this damage is the formation of free radicals, which trigger oxidative stress, compromise cellular integrity, and reduce the skin’s natural defense capacity. The use of skin protection products such as sunscreen serves as a preventive measure in daily skincare routines. This community service (PkM) activity was conducted through an interactive model of education and demonstration, aimed at enhancing public knowledge and awareness regarding the benefits of natural antioxidants available in sunscreen gel formulations derived from green tea leaf extract. The program was designed with an educational and participatory approach, in which the materials were delivered through theoretical explanations and simple practical demonstrations. The participants consisted of 25 individuals, both male and female, aged between 17 and 40 years, residing in the Lubuk Pakam area. The results of the activity showed a significant improvement in participants’ knowledge, with an average post-test score of 89.98 compared to a pre-test score of 56.05 indicating a substantial knowledge gain of 33.93 points, which falls into the "very high" category. This community outreach proved effective in increasing public understanding of the use of natural antioxidants in sunscreen products. Furthermore, participant satisfaction was remarkably high, with an average satisfaction rating of 96.4%, categorized as "Very Satisfied." In conclusion, this PkM activity successfully enhanced the participants’ knowledge regarding natural skin protection strategies, and participants expressed strong satisfaction with the implementation of the program.